Hadronic current correlation functions at finite temperature in the NJL model - Farias, RLS; Krein, G.; Battistel, O. A. (American Institute of Physics (AIP), 2004)
Recently there have been suggestions that for a proper description of hadronic matter and hadronic correlation functions within the NJL model at finite density/temperature the parameters of the model should be taken density/temperature dependent. Here we show that qualitatively similar results can be obtained using a cutoff-independent regularization of the NJL model. In this regularization scheme one can express the divergent parts at finite density/temperature of the amplitudes in terms of their counterparts in vacuum.